Donors for tax morale: Evidence from 34 African countries - Alessandro Belmonte; Vincenzo Bove; Jessica Di Salvatore (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Do aid projects affect citizens' motivation to pay taxes? We address this question by combining fine-grained data on aid projects from AidData and survey data from the Afrobarometer for 34 African countries. We first employ a subnational analysis, where the treatment varies by administrative unit, and then move to an individual-level analysis, which exploits the occurrence of a project during the Afrobarometer fieldwork. Two main results emerge: first, we find a negative impact of foreign aid on tax morale when projects provide public goods that people would have expected from the state; second, we estimate a positive effect when projects are aimed at building state capacity (e.g. tax cooperation). We additionally show that changes in tax morale are shaped by the donor's type and its adherence to transparency standards. Our research provides important insights for designing interventions that support tax capacity by identifying risk factors in current donors' practices.
Keywords: F35; H2; H11; O12; 330; foreign aid; tax morale; state capacity; public goods; Africa